How history's greatest pirates pillaged, plundered, and got away with it : the stories, techniques, and tactics of the most feared sea rovers from 1500-1800 /: the stories, techniques, and tactics of the most feared sea rovers from 1500-1800. (©2011) - Unknown
No abstract available